Does the Craniolateral Approach Provide Better Exposure to the Radius than the Craniomedial Approach for Internal Fracture Fixation in Dogs? - Lin, Kuan-Ting; Degner, Daniel A.; DeCamp, Charles E. (Veterinary and Comparative Orthopaedics and Traumatology, 2025)
To compare the exposure of the craniolateral approach (CLA) with craniomedial approach (CMA) of the radius in dogs. To make general observations of each approach that may affect the ease of fracture repair.Six canine cadavers were used in the study to compare the exposed surface area, length, and width of radius with CLA and CMA (n = 12).The CLA exposed a larger surface area of the radius compared with the CMA (p = 0.01). The CLA of the radius had greater proximal width compared with the CMA (p = 0.01). There was no significant difference in the length of exposed radii with either approach.The CLA provided greater exposure for internal fixation of the radius in dogs.
Keywords: canine radius; fracture repair; craniolateral approach; craniomedial approach